A comparative study of the effects of problem-solving skills training and relaxation on the score of self-esteem in women with postpartum depression - Nasiri, Saeideh; Kordi, Masoumeh; Gharavi, Morteza Modares (Iranian journal of nursing and midwifery research, 2015)
Self-esteem is a determinant factor of mental health. Individuals with low self-esteem have depression, and low self-esteem is one of main symptoms of depression. Aim of this study is to compare the effects of problem-solving skills and relaxation on the score of self-esteem in women with postpartum depression. This clinical trial was performed on 80 women. Sampling was done in Mashhad healthy centers from December 2009 to June 2010. Women were randomly divided and assigned to problem-solving skills (n = 26), relaxation (n = 26), and control groups (n = 28). Interventions were implemented for 6 weeks and the subjects again completed Eysenck self-esteem scale 9 weeks after delivery. Data analysis was done by descriptive statistics, Kruskal-Wallis test, and analysis of variance (ANOVA) test by SPSS software. The findings showed that the mean of self-esteem scale scores was 117.9 ± 9.7 after intervention in the problem-solving group, 117.0 ± 11.8 in the relaxation group, and 113.5 ± 10.4 in the control group and there was significant difference between the groups of relaxation and problem solving, and also between intervention groups and control group. According to the results, problem-solving skills and relaxation can be used to prevent and recover from postpartum depression.